The Impact Of Delivery Complications On Public Time At Basic Emergency Neonatal Obstetric Services Klaten District In 2019 - Rosalinna Rosalinna (Poltekkes Kemenkes Palembang, 2022)
Abstract Labor and postpartum complications often occur during and after delivery. Generally, severe complications will cause maternal death, but moderate or mild complications can cause maternal and postpartum morbidity. However, little research is available on the impact of postpartum and postpartum complications on women's lives. The method used in this study is a quantitative method with an analytic observational type of research with a prospective cohort approach. The sample in this study were mothers who gave birth vaginally at the Basic Emergency Neonatal Obstetric Services Public Health Center, Klaten Regency, both normal and complicated childbirth who had met the inclusion and exclusion criteria with a total of 57 respondents. .Data analysis used univariate and bivariate analysis with chi square test. The results of this study are that there is an impact of labor complications during the puerperium which is described as: there is a relationship between childbirth complications and prelactal feeding p value = 0.006, there is a relationship between labor complications and postpartum blues, p value = 0.01, and there is a relationship between labor complications and postpartum depression. partum, p value = 0.001. It is recommended for midwives to pay more attention to the postpartum period for mothers who experience childbirth complications